1995
DOI: 10.1002/poc.610081207
|View full text |Cite
|
Sign up to set email alerts
|

Hydride transfer reactions of leuco methylene blue and leuco thionine with some p‐benzoquinones

Abstract: The kinetics of the oxidation of leuco methylene blue and leuco thionine by some p‐benzoquinones were investigated spectrophotometrically by means of the stopped‐flow technique. Leuco methylene blue and leuco thionine were produced by photoreductions of methylene blue and thionine with triethylamine in ethanol in the drive syringe of the stopped‐flow apparatus and their solutions were used as such in the measurement of the oxidation rates. The kinetic isotope effect on the oxidation rate was observed. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Recently, we have studied the kinetics of the reactions of TH and MBH with two-electron oxidants by producing TH and MBH in a closed system by photoreductions of thionine (T ) and methylene blue (MB ) with triethylamine. 15 Kinetics, isotope effects and other evidence have proved that the reactions proceed through stepwise electron-proton-electron (EPE) transfer pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have studied the kinetics of the reactions of TH and MBH with two-electron oxidants by producing TH and MBH in a closed system by photoreductions of thionine (T ) and methylene blue (MB ) with triethylamine. 15 Kinetics, isotope effects and other evidence have proved that the reactions proceed through stepwise electron-proton-electron (EPE) transfer pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction occurs only in the micellar interior of the water pool, which accommodates both DMBQ and MBH. Reactions (4)-(7) were proposed for the hydride-transfer reaction between DMBQ and MBH in ethanol in a previous study [14]. According to the reaction mechanism proposed, the reactants DMBQ and MBH are in rapid equilibrium with a charge-transfer complex ((DMBQ−MBH)WP) which is also in rapid equilibrium with the radical ion pair (DMBQ − −MBH + ) formed by the reversible electron transfer from MBH to DMBQ in the complex (reactions (4) and (5)).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we studied the kinetics of the oxidation of leuco methylene blue (MBH) by some benzoquinones and the Fe 3+ ion spectrophotometrically by means of the stopped-flow technique [14,15]. Since MBH was known to be easily oxidized with dissolved oxygen, kinetic studies on the reactions of this compound with π-acceptors were not previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…The trifluoromethylation of 3-methylindole 38 proceeded with good yield at low catalyst concentration, when N,N,N′,N′-tetramethylenediamine (TMEDA) was used as an electron donor. In the presence of 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) as an electron donor, the reaction of terminal alkene 41 with Togni's reagent 39 also gave the hydrotrifluoromethylation product 42 in 67% yield as a major product, because the fully reduced form of MB, leuco-MB, acts as a hydrogen source [49]. The possible mechanism for the catalytic formation of CF 3 radical is shown.…”
Section: Methylene Blue and Acridine Redmentioning
confidence: 99%